PENGEMBANGAN RUANG TERBUKA HIJAU DENGAN PENDEKATAN KOTA HIJAU DI KOTA KANDANGAN - Jamilah Hayati; Santun R P Sitorus; Siti Nurisjah (TATALOKA, 2013)
According to Act No 26/2007 about Spatial Planning, each region is required to provide 30% of its territory as green open space (RTH), sharing of 20% as public RTH and 10% as private RTH. Ministry of Public Works introduced the Green City Development Program (P2KH) (Kementerian Pekerjaan Umum, 2012) to assist the implementation of the mandate of this Act. This study aims to identify and predict the needs of public RTH in Kandangan City and organize referrals for expansion using Green City approach. The needs of RTH is calculated based on vast territory, population and comfort index. Comfort index of Kandangan City are in comfortable range. Based on vast territory, it takes 735,39 ha land for public RTH. Based on population, Kandangan City requires 170,81 ha. Atribute of Gren City approach used is Green Open Space. Compared with Zoning, Regulation, there should be more area needed for public RTH as green belt.